2008
DOI: 10.1161/strokeaha.107.503821
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human S100B Exacerbates Brain Damage and Periinfarct Gliosis After Permanent Focal Ischemia

Abstract: Background and Purpose-We have previously demonstrated that augmented and prolonged activation of astrocytes detrimentally influences both the subacute and chronic phases of cerebral ischemia. Furthermore, we have suggested that the astrocyte-derived protein S100B may be important in these pathogenic events. However, the causal relationship between S100B and exacerbation of brain damage in vivo remains to be elucidated. Methods-Using transgenic mice overexpressing human S100B (Tg huS100B mice), we examined whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…Upon release, HMGB1 acts as an early proinflammatory cytokine within the NVU, which leads to exacerbation of proinflammatory responses, and blood-brain barrier breakdown in the ICH model [43,44]. S100B is released by activated astrocytes and is associated with enhanced reactive gliosis and further exacerbation of brain injury [45]. Increased S100B levels are also found after acute spontaneous ICH in patients, in association with acute worsening [46].…”
Section: Discussionmentioning
confidence: 99%
“…Upon release, HMGB1 acts as an early proinflammatory cytokine within the NVU, which leads to exacerbation of proinflammatory responses, and blood-brain barrier breakdown in the ICH model [43,44]. S100B is released by activated astrocytes and is associated with enhanced reactive gliosis and further exacerbation of brain injury [45]. Increased S100B levels are also found after acute spontaneous ICH in patients, in association with acute worsening [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings show that there is a significant correlation between S100B expression and the progression of neurodegenerative and other brain diseases, including cerebral ischemia, brain injury, Alzheimer's disease, Down syndrome, amyotrophic lateral sclerosis, schizophrenia, and depression (Rothermundt et al, 2003), so that astroglial S100B protein could be a sensitive marker of cerebral damage. Moreover, overexpression of S100B exacerbates brain damage and peri-infarct gliosis after focal ischemia (Mori et al, 2008), and arundic acid [(R)-(-)-2-propyloctanoic acid, ONO-2506], a novel agent that inhibits S100B synthesis in cultured astrocytes, and ameliorates ischemic brain damage (Tateishi et al, 2002) and cerebral amyloidosis and gliosis in a transgenic mouse model of Alzheimer's disease (Mori et al, 2006). TRPC3 could thus be a key upstream regulator of S100B expression and is a strong candidate protein for regulating the pathological activation of astrocytes induced by thrombin.…”
Section: Par-1-induced Astrocytic Responsesmentioning
confidence: 99%
“…In the experiment of cell culture, adding high concentration of S100B in nutrient solution could activate astrocytes and microglia to inhibit the expression of glial-derived nerve growth factor (GDNF) and reduce the neuroprotective effect of astrocytes, at the same time, promote inflammation factors releasing and exacerbate nerve cell damage [27]. Animal experiments showed that excessive expression of S100B could exacerbate brain ischemia injury in transgenic mice [28]. Clinical studies indicated that the concentration of S100B in CSF was highly correlated to the severity and prognosis of patients with acute ischemic stroke, the higher the concentration of S100B the worse the prognosis [29].…”
Section: Discussionmentioning
confidence: 99%